Epiphyseal separation of the proximal humerus in a preterm newborn - Rodrigues, Sara (2025)
Introduction: Epiphyseal separation of the proximal humerus at birth is a rare injury and its diagnosis can be challenging. Case report: A 28-week preterm newborn was delivered by emergency cesarean section. After a difficult extraction, the newborn presented with ecchymosis and swelling of the right shoulder and internal rotation of the right upper arm. Although the initial radiograph suggested shoulder dislocation, ultrasonography revealed epiphyseal separation of the proximal humerus. Discussion: Due to the unossified epiphysis in neonates, radiographic findings of epiphyseal separation may be misinterpreted as normal. Ultrasonography provides a more reliable diagnostic tool, allowing early and accurate identification. Given the high remodeling potential of the proximal humerus, these injuries are typically managed conservatively and have an excellent prognosis. Conclusion: This case highlights the importance of timely and accurate diagnosis of epiphyseal separation in newborns following traumatic birth. Prompt diagnosis allowed for conservative management of the patient, successfully preventing long-term sequelae.